Urban parks for people in a megacity: green spaces as social places in the twenty-first century Jakarta, Indonesia - MD Alwi, Najah (2020)
This thesis explores how the social experiences in urban parks and green spaces contribute to urban “conviviality” in the twenty-first-century city of Central Jakarta, Indonesia. Urban parks and green spaces are indispensable urban assets that help support the social sustainability of cities and potentially improve the quality of life of its citizens. Places that promote social cohesion through meaningful interactions between residents can improve the mental and physical well-being of residents. In the context of Asian megacities, where pressures on the development space are high, the socio-economic and cultural diversity of the population is significant, the governance and design of open green spaces, and the different ways that locals ‘produce’ space, is complex.